Entry Strategies into China: A Case Study of Three Benelux Technology Firms - Zhang, Ying; Ma, Binglum; Yue, Tao (Senate Hall, 2021)
In this case study, three technology-based companies from the Benelux area are introduced, with different sizes, ages, and backgrounds (Philips, SMS-Timing, and Trebu Technology). The companies have used different entry strategies into the Chinese market, ranging from exporting goods and services to setting up joint ventures with Chinese partner firms and setting up wholly-owned subsidiaries in China. The case study presents the experiences of the three companies with these different modes of internationalisation in the Chinese market. Advantages and disadvantages of each mode are discussed in light of the different characteristics of the three companies. The purpose of the case is to improve understanding of doing business on the Chinese market. This case can be widely used for MBA and undergraduate students in the studies of international strategy, entrepreneurship, and cultural management.
Keywords: China|internationalisation strategies